The influence of habitat on metabolic and digestive parameters in an intertidal crab from a SW atlantic coastal lagoon - Méndez, Eugenia (2021)
The hepatopancreas of decapod crustaceans is an organ which can act as indicator for digestive and metabolic parameters under different physiological and / or environmental conditions. However, biochemical studies on digestive and metabolic parameters of the hepatopancreas of euryhaline burrowing crabs such as Neohelice granulata from habitats with different diet compositions are still scarce. In the wild, adult males of N. granulata from Mar Chiquita Coastal Lagoon (Argentina) in mudflat habitat have diets with higher lipid and protein content than crabs from the saltmarsh, suggesting that diets could be an important factor influencing hepatopancreas activities. We tested this hypothesis here by exposing adult male crabs to a similar experimental diet and comparing hepatopancreas parameters for lipid components and protein metabolism between males from these two habitat types at different times (up to three months). At month 3, we noticed a decrease of the triglyceride concentration and lipase activity and an increase of protein concentration in crabs from the mudflat. In contrast, triglycerides and protein concentration did not change in crabs from the saltmarsh, while lipase activity decreased and levamisole insensitive AP increased at month 3. The results indicate that digestive and metabolic parameters in the hepatopancreas of crabs from habitats varying in diet content remain different, even if crabs are subsequently fed by a similar experimental diet. This suggests that specific intrinsic regulations of these hepatopancreas parameters could operate differently in each habitat and could not be changed by recent diet conditions.